Public Service: The Pillar of Responsive and Inclusive Governance in the Ministry of Religion - Langitan, Seska Vonny (Peneliti.net, 2025)
The public service is the main instrument in the realization of a democratic, just, and pro-community government. The Ministry of Religious Affairs of the Republic of Indonesia as an institution in charge of religious services and religious education has a strategic role in providing responsive and inclusive services. This article aims to examine the implementation of public services within the Ministry of Religious Affairs using a descriptive qualitative approach supported by a study of the theory of the New Public Service, the principles of good governance, and the theory of social justice. The findings show that the Ministry of Religious Affairs has implemented various innovations, such as digitalization of services, strengthening of information systems, and increasing service accountability. However, challenges still exist, especially related to the access gap in remote areas and digital literacy of the apparatus. Therefore, a continued commitment is needed to strengthen public service management that focuses on the needs of a pluralistic and diverse society.